Comparing the Effects of Victimization, School Connectedness, and Social Support on Heterosexual and Sexual Minority Adolescent Suicidality in the United States: A Partial Test of Minority Stress Theory - Mandatori, Flavia (Journal of interpersonal violence, 2023)
In the United States, sexual minority adolescents are among the subpopulations at the highest risk for suicide; yet, predictors of suicidality among this unique group remain significantly understudied. Drawing from Meyer’s minority stress theory (MST), this study examines whether general stressors act as predictors of adolescent suicidality and whether differences exist in the variation of these effects between heterosexual and sexual minority adolescents. Specifically, multivariate logistic regression models were developed to examine the impact that victimization, school connectedness, and social support have on heterosexual and sexual minority adolescent suicidality using a sample of 166,176 U.S. adolescents drawn from the 2019 Minnesota Student Survey. Participants ranged from 10 to 18 years of age and identified as heterosexual, bisexual, gay or lesbian, questioning, pansexual, queer, or as none of these. Findings highlight that sexual minorities (Exp(B) = 1.870, p < .001) were roughly twice as likely to report suicidality compared to their heterosexual peers. All victimization measures were highly predictive of suicidality among heterosexual and sexual minority adolescents. Overall, adolescents who were less connected to their school setting and more socially isolated were also more likely to experience suicidality; however, such effects were not reflected uniformly in every item measuring school connectedness and social support. Findings highlight important avenues for policies implementation aimed at mitigating the effects of multiple sources of stressors on adolescents’ mental health and reducing adolescents’ suicide rates. Interventions tailored to the unique needs of sexual minority adolescents are needed to address their disproportionate representation among those at risk for suicide.